Exploring the presence and effects of race inclusivity on branded content in social media - Langaro, D.; Cintra, M.; Marques, C. (2024 Global Fashion Management Conference at Milan, 2024)
Studying inclusion in advertising is of special interest, as it functions as a powerful tool for shaping individuals' attitudes towards cultural groups and their roles. Race inclusion, in particular, expressed by the diversity of skin tone, is important given the white-skinned dominant presence. This study analyses the actual representation of diverse skin tones in cosmetic brand publications on their Instagram pages. Moreover, it examines the impact of inclusive communication regarding skin tones on user engagement. A content analysis of 50 Instagram posts from 15 beauty brands was conducted, with a total of 750 posts inspected. Results indicate a lack of representation of skin tone diversity. Likewise, it was possible to conclude that diversity in skin tone negatively affects engagement, with darker skin tones performing worst among mass market cosmetic brands. Otherwise, diversity seems to be well accepted among audiences of premium brands. Implications for practice and theory are discussed